The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1063/1.331261
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam exposure characteristics of resists: Experimental results

Abstract: The exposure characteristics of six polymer resists to 1.5 MeV H+, He+, and O+ ions and to 20 keV electrons were measured. The resists used were polystyrene (PS), polymethyl methacrylate (PMMA), PMMA mixed with 20% of a copolymer of vinyl acetate and vinyl chloride (VMCC), poly(glycidyl methacrylate-co-3-chlorostyrene) (GMC), poly(butene-1-sulfone) (PBS), and a novolac. The deposited energy per unit volume required to expose a resist was found to be a function of the spatial energy dissipation rate of the ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(29 citation statements)
references
References 9 publications
4
22
0
2
Order By: Relevance
“…Based on this finding, the authors suggested that the energy density in the track, and not the total deposited energy is a measure of the ion's efficiency in modifying the film. Similar ideas were raised and discussed in more detail in the study of the exposure of polymer resists to 1.5 MeV H ϩ , He ϩ , and O ϩ ions 19 and in subsequent studies 5,6,20 for other polymeric systems. It should be noted that a different behavior was found for polystyrene 21,22 and PMDA-ODA ͑Ref.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Based on this finding, the authors suggested that the energy density in the track, and not the total deposited energy is a measure of the ion's efficiency in modifying the film. Similar ideas were raised and discussed in more detail in the study of the exposure of polymer resists to 1.5 MeV H ϩ , He ϩ , and O ϩ ions 19 and in subsequent studies 5,6,20 for other polymeric systems. It should be noted that a different behavior was found for polystyrene 21,22 and PMDA-ODA ͑Ref.…”
Section: Introductionmentioning
confidence: 87%
“…The need to consider the ion track structure in order to understand the damage induced in polymers by ion beams has been pointed out in the pioneering studies on exposure of resists 19 and electrical properties of ion-beam-irradiated organic films. 8 It was observed that 1 MeV He ϩ is around 50 times less efficient in producing resistivity drop in NiPC compared to 1 MeV Ar ϩ , although their (dE/dx) e differ by only a factor of 4.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the mass density of the polymer film (-3) and the fraction of the -2 gm film that contains unpaired spins (-1/7) leads to a rough estimate of -5 x 1020 spins/cm 3 for PPO implanted to 10 1 6 cm-2 with 200 keV "°Br ions. A comparison of this spin density with the carrier density deduced from the optical transmission data suggests that only a fraction of these carriers have unpaired spins [14].…”
Section: Discussionmentioning
confidence: 99%
“…Of significance is the higher sensitivity of the polymer (by -2 orders of magnitude) to ion beams relative to electron beams, so that ion beam lithography is feasible at fluences of less than 10 cm- [3]. For positive resists (e.g., PMMA), ion implantation results in scission of the molecular chains, while for negative resists (e.g., polystyrene), implantation results in crosslinking of polymer chains.…”
Section: Acmmentioning
confidence: 99%
“…11 It is easily visible and can be followed even by the naked eye in the film. At this very high fluence the The financial support from C.N.R.…”
mentioning
confidence: 98%